Analisis perlakuan akuntansi aset tetap pada Badan Pengelolaan Keuangan Dan Pendapatan Daerah Kabupaten Kepulauan Sangihe berdasarkan Permendagri No 1 tahun 2019 - Darea, Tania Wilhelmina; Tinangon, Jantje J.; Warongan , Jessy D. L. (Yayasan Widyantara Nawasena Raharja, 2025)
Fixed assets play a crucial role in government financial reporting at both central and regional levels, as they represent resources that must be safeguarded and managed responsibly. This study analyzes the accounting treatment of fixed assets at the Regional Financial and Revenue Management Agency of Sangihe Islands Regency in accordance with the Indonesian Ministry of Home Affairs Regulation No. 1 of 2019. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation. The findings indicate that the depreciation of regional assets covers various types of fixed assets, including buildings, official vehicles, office equipment, and public facilities. Depreciation is determined based on estimated useful life, residual value, and the straight-line method. However, the depreciation calculations have not fully complied with the prescribed regulations. Registration and disclosure of fixed assets are conducted through the agency’s financial statements to enhance transparency and accountability in regional asset management. This study highlights the importance of implementing standardized accounting practices to ensure accurate and reliable financial reporting of government fixed assets.